Commodity finance: a commercial proposition? Micro- and Mesofinance for Agricultural Commodity Production, Processing and Trade - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2003)
This Conference brings together the financial experience of rural and agricultural microfinance institutions and the experience of the Common Fund and other agencies with promoting commodities and small and micro-entrepreneurs producing, processing and marketing commodities. We expect that this will result in: – the further growth and development of sustainable financial services; and – the further growth and development of sustainable commodity-related enterprises. These two objectives – the growth of profitable local financial institutions and of profitable local enterprises – are interrelated and mutually reinforcing. There is one lesson to be learned from the now developed industrial countries: Focusing in an early stage of development on the poor, who largely depend on commodities, means focusing on a huge future market. We hope to get this message across to large numbers of financial institutions.
Keywords: 330; Rohstoffabkommen; Agrarkredit; Mikrofinanzierung; Landwirtschaftliche Entwicklung; Welt; Entwicklungsländer; Fund for Commodities